Mechanical and Biological Complications Two Years After Full-Arch Implant-Supported Prosthetic Rehabilitation: A Retrospective Clinical Study - Denisa Tabita Sabău; Petra Saitos; Rahela Tabita Moca; Raluca Iulia Juncar; Mihai Juncar (Clinics and Practice)
Background/Objectives: Full-arch implant-supported prostheses have become a widely accepted solution for edentulous patients, yet long-term biological and mechanical complications remain a clinical concern. Methods: This retrospective study included 70 fully edentulous patients (362 implants) rehabilitated with either fixed or removable implant-supported prostheses. Data were collected on demographics, medical status, type and location of prostheses, implant type, abutments, method of fixation, and complications. Statistical analysis included Fisher’s exact test, the Mann–Whitney U test, and chi-squared tests, with a significance level set at p < 0.05. Results: Mechanical complications occurred in 41.4% of patients (29 out of 70), with framework fractures reported in eight cases (27.6%), ceramic chipping in six cases (20.7%), and resin discoloration in four cases (13.8%). The prostheses were fabricated using monolithic zirconia, metal–ceramic crowns, zirconia on titanium bars, and hybrid resin/PMMA on cobalt–chromium frameworks. Gingival inflammation was also noted in 41.4% of cases (n = 29), predominantly in posterior implant regions. Younger patients and those without systemic diseases showed a significantly higher incidence of mechanical complications. Conclusions: Two years post-treatment, mechanical and biological complications appear to be independent phenomena, not significantly associated with most prosthetic variables. Patient-specific factors, particularly age and general health status, may have greater predictive value than prosthetic design. Limitations of the study include its retrospective design and the lack of radiographic data to assess peri-implant bone changes.